Dampak digitalisasi pada pengumpulan pajak dan pertumbuhan pendapatan guna mengoptimalkan kesadaran pajak di Indonesia - Pratama, Andri (Maliki Interdisciplinary Journal, 2024)
This study aims to determine the impact of digitalization of tax collection and state revenue growth. In addition, it also aims to optimize tax awareness in Indonesia. This research adopts a descriptive qualitative approach by using the "library research" method to collect data through an in-depth literature study, with the aim of presenting a comprehensive analysis of the topics discussed. Tax digitalization in Indonesia has significantly improved tax collection efficiency and state revenue growth through e-Filing, e-Billing, and e-Invoice systems that facilitate the process and increase transparency, although there are still challenges such as limited technological infrastructure and digital literacy that need to be overcome by improving infrastructure and educating taxpayers.